Penggunaan Penggunaan Metode SAS (Struktural Analitik Sintetik) untuk Meningkatkan Keterampilan Membaca Permulaan Kelas II - Tanti Indriyani Kardi; Henry Aditia Rigianti; Heru Purnomo (Balai Diklat Keagamaan Semarang, 2025)
This research aims to improve beginning reading skills using the SAS (Synthetic Structural Analytical) method. This research uses the Classroom Action Research (PTK) method. This research was conducted at Sembungan State Elementary School with class II student respondents. This Classroom Action Research (PTK) was carried out in 2 cycles. This research shows the results that the percentage of students' initial reading skills from initial conditions, cycle 1 and cycle 2 has increased from 38.47% to 76.92%. The indicator of success of this research is that if the percentage of students exceeds 75% then this Classroom Action Research has been successful. The conclusion of this research is that the initial reading skills of class II students at SD Negeri Sembungan have improved after using the SAS method.